A new species of Celestus from west-central Panama, with consideration of the status of the genera of the Anguidae: Diploglossinae (Squamata) - Jay M Savage; Karen R Lips; Roberto Ibáñez D (Revista de Biología Tropical, 2008)
A recently discovered new species of diploglossine lizard is described from west-central Panama. The distinctiveness of the nominal genera Celestus and Diploglossus is confirmed; the new form represents the southernmost record for the genus Celestus. A summary of selected characteristics and general distribution is presented for all recent species of diploglossines, including members of the Antillean genera Saurisia and Wetmorea and the South American genus Ophiodes. A systematic key to mainland members of the genus Celestus is provided. Rev. Biol. Trop. 56 (2): 845-859. Epub 2008 June 30. Se describe una especie nueva de lagarto diploglossino recientemente descubierta en el centro-oeste de Panamá. Confirmamos la peculiaridad de los géneros nominales Celestus y Diploglossus. La nueva especie representa el registro más al sur del género Celestus. Se presenta un resumen de características selectas y de la distribución general de todas las especies recientes de diploglossinos, incluyendo a los miembros de los géneros antillanos Saurisia y Wetmorea y del género suramericano Ophiodes. Se provee una clave sistemática para los miembros de tierra firme del género Celestus.